Sportonomics - The Influence of Money to the Sports - Shekjerov, Paskal; Halík, Jaroslav, 1961-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Rektorát (2013)
In this master thesis the main focus is directed towards the analysis of the interconnection between the sports and the economics from several different aspects and their interdependence of each other. This was enabled by the introduction of the concept of "Sportonomics", with the main concern on the relationship between the money and the sports, by taking into account different perspectives, such as the direct influence of money to the success, the growing significance of the financial component to the sports, analyzed through the comparisons between leagues (clubs) across the continent including their financial construction, then covering the commercialization of the sports and the on-going movements as an opposition to this trend of commercialization of the sport. Regarding the structure of the thesis and its chapters, in the first chapter it starts off with the most unattractive sport among the ones covered in the thesis by focusing on the financial strength and the actual performances of the clubs in some of the strongest domestic handball competitions in Europe (Bundesliga, ASOBAL, Division 1, Elitserien), as well as including an overview over the emerging new forces from Eastern Europe and the increasing competitiveness posed to the established Western European clubs. In the second chapter, as it moves on towards the sports enjoying higher degree of popularity and investments, there is the basketball game as the main subject of analysis. This part provides an overview of the situation on club and individual (player) level for both the Euroleague and the NBA, as well as clarification of the "salary cap" policy in terms of the limited spending on players' salaries within one team. The last chapter in the thesis, concentrates on the most popular and the most capital intensive sport, the football, with it attracting lots of investors and lots of money being circulated throughout this "market".
First, it startx off the analysis with an overview over the top 10 clubs on the continent in terms of their revenues, with additionally taking a detailed look at their revenues structure, by dividing it into different subcategories. Later, it continues with an overview of the situation at the European level by including the Eastern European sides as well, before moving to the sensitive subject of the growing commercialization of the game and focusing of some sky-high figures and numbers surrounding the sport itself. As an addition to this subject, it continues with the movement set as a opposition to this trend, named as "Against Modern Football', and providing few examples as well as the exact reasons behind this movement fighting against the commercialization of the game. As last point in this third final chapter, it covers the UEFA "financial fair play", as a policy undertaken by the continent's official football association with the aim of limiting the on-going inflation in the football market as well as regulating the financial activity of the clubs involved into its membership. In the end there are several conclusions based on the overview of what has been covered within the master thesis. A look has been taken at the relationship between the money and the sports from two different standpoints and perspectives. Firstly, it is the sport's perspective, through the relationship between the money involved in running a club and the success coming out of it as an output as well as the correlation between the two of them, and then taking into account the second perspective by focusing on the business component and the impact of the money to the nature of the sports i.e. the commercialization of the game. Regarding the sport's perspective and the relationship between the money invested and the specific success on the field/court, as it can be concluded by the analysis of all the three sports (handball, basketball, football) included in the thesis, there is a findin
Vedoucí práce: Jaroslav Halík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Rektorát, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses